Management Accounting / Principles & Practice - Upchurch Alan (Financial Times - Prentice Hall, 1998)
This book has been developed to provide an accessible and readable introduction to Management Accounting.
Preface, Acknowledgements, Fundamentals, Introduction, The Management Accounting Framework, Cost Estimation, Absorption of Overheads, Absorption Costing and Marginal Costing, Decision Analysis, Cost/ Volume/ Profit Analysis, Relevant Costs and Benefits for Decision Making, More Decisions: Price-Setting and Limiting Factors, Decision Making Under Conditions of Risk and Uncertainty, Capital investment Appraisal, Capital Investment Appraisal, Capital Investment Appraisal: Further Issues, Planning and Control and Performance Evaluation, Budgetary Planning, Budgetary Control, Analysis of Variances, Performance Appraisal, Behavioural Considerations, Glossary, Appendices, Index.